The The Influence Of Financial Literacy, Socioeconomic Status Of Parents And Lifestyle On Student Financial Behavior - Fajar Abriyanto; Tina Miniawati Barusman (International Journal of Economics, Business and Innovation Research, 2024)
Financial behavior is an important skill that needs to be mastered by every individual, including university students. Financial behavior is influenced by various factors, including financial literacy, parents' socioeconomic status, and lifestyle. This study aims to analyze whether financial literacy, socioeconomic status of parents and lifestyle significantly affect the financial behavior of students of the Faculty of Economics and Business, Bandar Lampung University. The data used in this study are quantitative data obtained directly from the respondent's source. The primary data used was collected using a questionnaire, the population in this study amounted to 269 students but the researchers did not conduct research with the entire population so the researchers used the Solvin formula, based on the calculation results, the number of samples used amounted to 72 students. All data were analyzed using multiple linear regression analysis techniques partial hypothesis test (t test), simultaneous hypothesis test (F test), and determination coefficient test (R2) using the help of the spss application. The findings of this study that financial literacy and lifestyle have a significant effect on student financial behavior while the socioeconomic status of parents has no significant effect on student financial behavior. Taken together, financial literacy, socioeconomic status of parents, and lifestyle have a significant effect on student financial behavior.